Influência das incertezas de medição no cálculo de equivalentes de redes aplicados nos estudos de estabilidade de tensão - Felipe de Sousa Silva (2015)
During real time operation, power system Voltage Stability evaluation isnormally based on Network Equivalents. These equivalents are in general calculated from voltage and current phasor values, in particular those obtained from the so-called Phasor Measurement Systems. In spite of the hightechnology feature of these systems, measurements uncertainties must be taken into account. These uncertainties characterize the measurement error named noise that can negatively affect the equivalent results. In this context, the work investigates the effect of the noise on equivalent calculation and the consequent impact on voltage stability analyses. As a result of the research, this master thesis presents a computational tool, the SimC Power SystemScenarios Simulator. Its objective is to create groups of voltage and current phasor measurements, considering noise presence, to provide several and different scenarios for voltage stability investigations.